1998
DOI: 10.1080/10236249809387068
|View full text |Cite
|
Sign up to set email alerts
|

The result of evolutionary limb loss on the complement of motor neurons in a crayfish limb nerve revealed by serial homology

Abstract: Many macruran decapod crustaceans show sexual dimorphism of abdominal appendages adapted for use as secondary reproductive organs. Not only does the Australian crayfish, Cherax destructor, show no external, abdominal dimorphism, but both males and females have lost the pleopods of the first abdominal segment entirely. The first nerves of the abdominal ganglia of crayfish and lobsters carry the axons of the pleopod motor neurons. We used intracellular cobalt infusion into the first nerves of the first and secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Even in animals that lack swimmerets on the first abdominal segment, there are neurons with axons in the ganglion's N1 that look like swimmeret motor neurons. Drummond et al (1998) used cobalt backfilling methods in Cherax destructor to compare the population of neurons in A1 with those in ganglia that innervate unmodified swimmerets and reported that the numbers of neurons in A1 were much reduced. Page (1985) used similar methods to compare the innervation of the sexually-dimorphic swimmerets of Homarus americanus .…”
Section: Modular Organization and Local Circuits In The Cnsmentioning
confidence: 99%
“…Even in animals that lack swimmerets on the first abdominal segment, there are neurons with axons in the ganglion's N1 that look like swimmeret motor neurons. Drummond et al (1998) used cobalt backfilling methods in Cherax destructor to compare the population of neurons in A1 with those in ganglia that innervate unmodified swimmerets and reported that the numbers of neurons in A1 were much reduced. Page (1985) used similar methods to compare the innervation of the sexually-dimorphic swimmerets of Homarus americanus .…”
Section: Modular Organization and Local Circuits In The Cnsmentioning
confidence: 99%